Practice and Learning: Spatiotemporal Differences in Thalamo-Cortical-Cerebellar Networks Engagement across Learning Phases in Schizophrenia - Korostil, Michele; Remington, Gary; McIntosh, Anthony Randal (Frontiers in Psychiatry, 2017)
Background: Understanding how practice mediates the transition of brain-behavior networks between early and later stages of learning is constrained by the common approach to analysis of fMRI data. Prior imaging studies have mostly relied on a single scan, and parametric, task-related analyses. Our experiment incorporates a multisession fMRI lexicon-learning experiment with multivariate, whole-brain analysis to further knowledge of the distributed networks supporting practice-related learning in schizophrenia. Methods: Participants with schizophrenia were compared with healthy control participants as they learned a novel lexicon during two fMRI scans over a several-day period. All participants were trained to equal task proficiency prior to scanning. Behavioral-Partial Least Squares, a multivariate analytic approach was used to analyse the imaging data. Permutation testing was used to determine statistical significance; bootstrap resampling was used to determine the reliability of the findings. Results: With practice, healthy control participants transitioned to a brain-accuracy network incorporating dorsostriatal regions in late learning stages. The schizophrenia participants did not transition to this pattern despite comparable behavioral results. Instead, successful learners were differentiated primarily on the basis of greater engagement of perceptual and perceptual-integration brain regions Conclusions: There is a different spatiotemporal unfolding of brain-learning relationships in schizophrenia. In schizophrenia, given the same amount of practice, the movement from networks suggestive of effortful learning towards subcortically-driven procedural ones differs from healthy control participants. Learning performance in schizophrenia being driven instead by varying levels of engagement in perceptual regions suggests that perception itself is impaired in the illness and may impact downstream, ‘higher level’ cognitive impairment.